Aspects Hindering the Development and Survival of Small and Medium-Sized Enterprises in Pakistan: Stability Perspective - Ali, Shoaib (Asian Journal of Economics and Empirical Research, 2021)
This article intends to explore aspects that are hindering the development and survival of small and medium-sized enterprises (SMEs) in Pakistan. A survey was developed to collect statistics from 226 SME owners and staff in selected Punjab Provinces in Pakistan. Some statistical approaches accompanied the results of the survey to examine the elements hindering the development of SMEs in Pakistan. The results of the research indicate that the expected constraints, including lack of management knowledge, corruption, decaying infrastructure, absence of financial funds, and inadequate earnings are hindering SME development and survival in Pakistan. Considering the elements hindering the development will help legislators, federal and local concerns, NGOs, shareholders, policymakers, and others to create well-structured policies and plans that will aggressively promote the efficiency and stability of SMEs in Pakistan. The significance of this research derives from the reality that few studies have been conducted about the development and survival of SMEs in Pakistan with a stability perspective.